C-reactive protein 2 days after laparoscopic gastric bypass surgery reliably indicates leaks and moderately predicts morbidity - Warschkow, René; Tarantino, Ignazio; Folie, Patrick (Journal of gastrointestinal surgery, 2012)
BackgroundThe aim of the present study was to evaluate whether serum C-reactive protein (CRP) is a useful predictor of early post-operative complications, particularly of intestinal leaks after laparoscopic Roux-en-Y gastric bypass (LRYGB) surgery.MethodsThe present study was a retrospective analysis of a prospectively maintained database with 809 patients who underwent LRYGB from 2002 until 2011. For 410 of these patients, at least one CRP measurement within the first seven post-operative days was available. The diagnostic value was determined by the area under the curve (AUC) of the receiver operating characteristic (ROC) curve.ResultsForty-nine of 410 patients (12.0 %; 95 % confidence intervals [95 % CI], 9.2-15.5 %) developed surgery-related complications. Leaks occurred in 17 patients (4.1 %; 95 % CI, 2.6-6.5 %) at a median of 5 days after surgery. CRP levels 2 days after surgery showed the highest diagnostic value for post-operative complications (AUC, 0.74; 95 % CI, 0.60-0.89). Sensitivity was 0.53 (95 % CI, 0.31-0.74) and specificity was 0.91 (95 % CI, 0.79-0.96) on day 2 (cutoff level, 229 mg/l). The sensitivity for intestinal leaks was 1.00 (95 % CI, 0.51-1.00).ConclusionCRP on post-operative day 2 is a valuable predictor of post-operative complications, in particular intestinal leaks. Radiological imaging studies for intestinal leaks could be restricted to patients with CRP values exceeding 229 mg/l.